Evaluating the Noise Exposure Rate and the Relationship between Job Stress and Sleep Disturbance in Workers of one of the Iranian Construction Industry - Ehsan Asivandzadeh; Zeynab Jamalizadeh; Afshin MOHEBI; Peyman YARI; Seyyed Poorya FAZELI (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Noise is considered as a risk factor for a wide range of industrial environments, including construction industry. The aim of this study was to determine the relationship between job stress due to noise exposure with sleep disturbance. Methods: This descriptive-analytic study was carried out among 134 workers of one of the construction industry in the country. For assessment of noise exposure of individuals, in accordance with ISO 9612: 2009 was measured by the occupational exposure level of 8 hours. To assess occupational stress, the Parker Job Stress Questionnaire and Epworth's (Epworth) Questionnaire were used to assess sleep disturbance. Data were analyzed using Kolmogorov-Smirnov test, Pearson correlation test and multivariate regression in SPSS version 23 software. Results: The results of Pearson correlation test and multivariate regression showed that noise can cause sleep disturbance by causing occupational stress in workers. Based on the results of this study, noise exposure, occupational stress and sleep disturbance have a direct and positive relationship. With increasing in noise exposure, occupational stress and sleep disturbance also increases. Conclusion: Assessing the noise exposure of workers in the construction industry has shown that noise is a very important factor in the psychological problems of workers in this industry. In addition to the direct effects of noise on sleep disturbance, it can indirectly exacerbate sleep disturbances. This article confirms the necessity to pay attention to the conditions of this work group.